The Role of Students’ Beliefs When Critically Reasoning From Multiple Contradictory Sources of Information in Performance Assessments - Zlatkin-Troitschanskaia, Olga; Beck, Klaus; Fischer, Jennifer; Braunheim, Dominik; Schmidt, Susanne; Shavelson, Richard J. (Frontiers in Psychology, 2020)
Critical reasoning (CR) when confronted with contradictory information from multiple sources is a crucial ability in a knowledge-based society and digital world. Using information without critically reflecting on the content and its quality may lead to the acceptance of information based on unwarranted claims. Previous personal beliefs are assumed to play a decisive role when it comes to critically differentiating between assertions and claims and warranted knowledge and facts. The role of generic epistemic beliefs on critical stance and attitude in reflectively dealing with information is well researched. Relatively few studies have been conducted on the influence of domain-specific beliefs, i.e. beliefs in relation to specific content encountered in a piece of information or task, on the reasoning process, and on how these beliefs may affect the information-processing and decision-making processes. This study focuses on students’ task- and topic-related beliefs that may influence their reasoning when dealing with multiple and partly contradictory sources of information. To validly assess CR among university students, we used a newly developed computer-based performance assessment in which the students were confronted with an authentic task which contains theoretically defined psychological stimuli for measuring CR. To investigate the particular role of task- and topic-related beliefs on CR, a purposeful sample of 30 university students took part in a performance assessment and then were interviewed immediately afterwards. In the semi-structured cognitive interviews, the participants’ task-related beliefs were assessed. Based on qualitative analyses of the interview transcripts, three distinct profiles of decision-making among students have been identified. More specifically, the different types of students’ beliefs and attitudes derived from the cognitive interview data suggest their influence on information processing, reasoning approaches and decision-making. The results indicated that the students’ beliefs had an influence on their selection, critical evaluation and use of information as well as on their reasoning processes and final decisions.